PENGARUH PERSONAL BACKGROUND, POLITICAL BACKGROUND DAN PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PERAN DPRD DALAM PENGAWASAN KEUANGAN DAERAH (STUDI KASUS DI KARESIDENAN SURAKARTA DAN DAERAH ISTIMEWA YOGYAKARTA TAHUN 2006) - JAKA WINARNA; SRI MURNI (Jurnal Bisnis dan Akuntansi, 2007)
This research aims to examine the influence of personal background, political background, and council budget knowledge towards the role of DPRD on region financial control. This research is motivated by the fact that individual background will effect to individual behavior on political activity. Dependent variables in this research are personal background, political background, and council budget knowledge towards the role of DPRD on region financial control. Independent variable is the role of DPRD on region financial control in planning, implementing, and responsibility steps. The data in this research consist of primary data that taken from questionnaires distributed directly to respondents. The collected are from 85 respondents that Financial Commission and Budget Commitee members of DPRD at ex Surakarta Residence and Yogyakarta. Hypothesis of this research are tested by using Multivariate Analysis of Variances (MA-NOVA). The result of this research in general shows that personal back-ground, and political background have no significant influence towards the role of DPRD on region financial control. But the council budget know-ledge have significant influence towards the role of DPRD on region finan-cial control.